Phase engineering of dual active 2D Bi2O3-based nanocatalysts for alkaline hydrogen evolution reaction electrocatalysis. Issue 2 (15th December 2021) - Wu, Ziyang; Mei, Jun; Liu, Qiong; Wang, Sen; Li, Wei; Xing, Shihui; Bai, Juan; Yang, Jianping; Luo, Wei; Guselnikova, Olga; O'Mullane, Anthony P.; Gu, Yuantong; et al.
Abstract : In situ fabricated Bi2 O3 nanosheets with both α-Bi2 O3 and Bi x Ni alloy phases, simultaneously contributing to the water dissociation step and the hydrogen formation step, demonstrate high HER electrocatalytic activity in alkaline media. Abstract : In electrochemical water splitting, the balance between water dissociation step and the hydrogen adsorption on the catalysts is an ongoing challenge. Herein, Bi2 O3, an inactive catalyst for the hydrogen evolution reaction (HER) caused by its unfavourable hydrogen adsorption Gibbs free energy (Δ G H* ), is activated by an in situ phase engineering strategy for efficient HER electrocatalysis in alkaline media. Through this strategy, two-dimensional (2D) dual active Bi2 O3 nanosheets with both Bi x Ni alloy phases and α-Bi2 O3 were fabricated to simultaneously catalyse the water dissociation step and the hydrogen formation step during an alkaline HER. In combination with the advantages of 2D nanomaterials and dual active catalytic sites, this phase engineered Bi2 O3 -based catalyst exhibited much improved alkaline HER performance. The modulated catalyst demonstrated an overpotential of 127 mV (at j = 10 mA cm −2 ) and a Tafel slope of 92 mV dec −1 in 1 M KOH, and is exceptional compared with other Bi2 O3 -based HER electrocatalysts. This work not only provides an innovative way to activate HER-inferior bismuth-based catalysts, but also offers new insights into the design of dual active catalysts for sluggish alkaline HER catalysis.